2005
DOI: 10.1103/physreve.71.056102
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous roughness with system-size-dependent local roughness exponent

Abstract: We note that in a system far from equilibrium the interface roughening may depend on the system size which plays the role of control parameter. To detect the size effect on the interface roughness, we study the scaling properties of rough interfaces formed in paper

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The dynamics of correlation buildup in these physical systems, and their other properties, can then be explored with the use of surfacegrowth methodologies. Numerous examples of such studies, experimental as well as theoretical and computational, come from a variety of fields such as tumor-growth processes [1] in cancer research, growth of cell colonies [2] in biophysics, roughening of lipid bilayers [3] in softmatter biomaterials, dynamics of combustion fronts [5], imbibition processes [4], film-growth processes [6], timeseries and market price analyses in econo-physics [7], and scalability and synchronization of parallel-computing system [8,9] in computer science, to give representative examples.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of correlation buildup in these physical systems, and their other properties, can then be explored with the use of surfacegrowth methodologies. Numerous examples of such studies, experimental as well as theoretical and computational, come from a variety of fields such as tumor-growth processes [1] in cancer research, growth of cell colonies [2] in biophysics, roughening of lipid bilayers [3] in softmatter biomaterials, dynamics of combustion fronts [5], imbibition processes [4], film-growth processes [6], timeseries and market price analyses in econo-physics [7], and scalability and synchronization of parallel-computing system [8,9] in computer science, to give representative examples.…”
Section: Introductionmentioning
confidence: 99%
“…These exponents determine the universality class of kinetic roughening process under consideration. 3 While the self-affine and self-similar roughness of growing interfaces was observed in many physical systems (see [11][12][13][14][15]), more generally, the scaling behavior of local surface width, sðDxÞ / ðDxÞ z 2 , is characterized by the local roughness exponent z 2 , which is less or equal to the global roughness exponent, i.e., z 2 a [47][48][49][50][51][52][53][54]. The case of z 2 = a = H corresponds to self-affine (or self-similar, if z 2 = a = H = 1 [45]) surfaces, whereas surface roughness characterized by z 2 < a is termed as an ''anomalous'' roughness [47] and it is characterized by three or more independent scaling exponents, e.g., z 2 , a, and z, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The Family-Vicsek and generic scaling dynamics are observed in a grain variety of physical systems [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However, in many cases the local geometry of the interface is not pure self-similar or self-affine, rather than multi-fractal [20,22,23,[55][56][57][58] or multiaffine [59][60][61][62][63][64][65]. The multiscaling properties of such interfaces can be investigated by calculating the q-order height-height correlation function defined as…”
Section: Introductionmentioning
confidence: 99%
“…x=0 |z(x) − z(x + x)| q ) 1/q (see, for details, Ref. [33]). Furthermore, in contrast to the increase of global front width W ∝ t α expected in the case of kinetic roughening and always observed in paper imbibition experiments at a constant humidity [4][5][6][7][8][9][10], we found that the global width of the wetting front moving in regime (3) tends to decrease in time (see Fig.…”
mentioning
confidence: 99%